Metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material, preparation method and photocatalytic CO2 reduction application
By using metalporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite as photocatalyst, the problem of low yield of photocatalyst CO2 reduction in ethylene in the prior art is solved, and high-efficiency photocatalyst reduction of CO2 is achieved to prepare high-value-added products effect.
Patent Information
- Application Number
- CN202510051820.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the yield of ethylene in the high value-added products prepared by photocatalytic CO2 reduction is relatively low, making it difficult to achieve carbon-carbon coupling and efficient electron transfer of C1 intermediates.
Using metalporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite as photocatalyst, metalporphyrin compounds are coupled with triazine derivatives or 1,8-octanediol with alkynyl groups. Reaction or coupling reaction forms a conjugated microporous polymer and is compounded with bismuth oxyhalide to form a heterojunction structure.
The yield of C2 compounds with higher added value such as ethylene is improved by photocatalytic reduction of CO2, which is used to prepare C2 compounds with higher added value, enhance light absorption performance and photocatalytic activity, and improve the chemical stability and semiconductor performance of the catalyst.
Smart Images

Figure CN119456038A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible metalloporphyrin conjugated organic polymer-halogen oxybismuth composite material and a preparation method and application thereof. Background Art
[0002] In the existing technology, artificial photosynthesis uses sunlight as energy to reduce CO2 into high-value-added products such as carbon monoxide, methane, and ethylene. However, due to the high conversion energy barrier, the yield of ethylene in the high-value-added products prepared by photocatalytic CO2 reduction is relatively low. The key to increasing the yield of ethylene is the preparation of efficient photocatalysts.
[0003] Generally, the photocatalytic process includes three steps: light capture, electron-hole separation, and redox reaction. Based on the photocatalytic CO2 reduction mechanism, it is generally believed that photocatalysts for efficient CO2 photoreduction need to have several characteristics: (1) a suitable energy band combined with strong light absorption ability to achieve efficient use of solar energy; (2) strong chemical adsorption ability for CO2; (3) high photogenerated electron-hole separation efficiency, which helps to generate a sufficient concentration of free electrons to ensure the continuous and efficient CO2 reduction reaction.
[0004] Metalloporphyrins are nitrogen-containing compounds with a π-electron conjugated ring structure, which is conducive to the transfer of photogenerated electrons. In addition, most metalloporphyrins and their derivatives have good optical properties. However, a single metalloporphyrin cannot effectively cause carbon-carbon coupling of C1 intermediates, so the CO2 reduction products are mainly limited to C1 compounds, such as CO, CH4 and CH3OH, and the production of C2 compounds with higher added value, such as ethane and ethylene, is low, which greatly limits its application in the field of photocatalysis. Summary of the invention
[0005] In view of the above-mentioned technical problems existing in the prior art, the purpose of the present invention is to provide a metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material and a preparation method and application thereof. The metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material provided by the present invention can well solve the technical problem that the catalysts in the prior art are difficult to achieve carbon-carbon coupling of C1 intermediates and efficient electron transfer, resulting in the CO2 reduction product being mainly limited to C1 compounds.
[0006] The synthesis mechanism of the metal porphyrin-based conjugated organic polymer of the present invention is that the aromatic halogen atom in the metal porphyrin compound and the alkynyl group of the triazine derivative with the alkynyl group form a carbon-carbon bond through a ball-head coupling reaction to obtain a conjugated microporous polymer; or the metal porphyrin compound and 1,8-octanediol undergo an Ullmann reaction, and the hydroxyl group and the aromatic halogen atom couple to obtain a conjugated microporous polymer.
[0007] The technical solution adopted by the present invention is as follows: A metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material, wherein the composite material is a heterojunction structure formed by compounding bismuth oxyhalide and metal porphyrin-based conjugated organic polymer, wherein the metal porphyrin-based conjugated organic polymer is formed by coupling reaction between aryl halogen atoms in metal porphyrin compounds and alkynyl groups of triazine derivatives with alkynyl groups, or is a conjugated microporous polymer formed by coupling reaction between aryl halogen atoms in metal porphyrin compounds and hydroxyl groups of 1,8-octanediol; the central metal ion in the metal porphyrin compounds is a Cu, Co or Fe metal element; the bismuth oxyhalide is a crystalline layered structure formed by alternating stacking of bismuth oxygen layers and halogen layers, wherein the layers are connected by van der Waals forces, and BiO6 in the bismuth oxygen layers is an octahedral structure, wherein X represents Cl, Br or I halogen elements.
[0008] Furthermore, the preparation method of the metalloporphyrin conjugated organic polymer comprises the following steps: 1) Metalloporphyrin compounds and triazine derivatives with alkynyl groups or 1,8-octanediol are dissolved in an organic solvent containing triethylamine; 2) adding catalysts cuprous iodide and bis(triphenylphosphine)palladium dichloride; 3) Heat the oil bath to 60-120°C under nitrogen atmosphere and continue stirring for 6-24 hours; 4) Step 3) After the reaction is completed, the product is filtered, washed and dried to obtain the metalloporphyrin conjugated organic polymer.
[0009] Furthermore, in step 1), the molar ratio of the metal porphyrin compound to the triazine derivative with an alkynyl group or 1,8-octanediol is 1.1-1.5:1, the volume ratio of the triethylamine to the organic solvent is 0.5-2:1, and the dispersed concentration of the metal porphyrin compound in the reaction solution of step 1) is 0.002-0.02 mol / L.
[0010] Furthermore, the metal porphyrin compound uses 5,10,15,20-tetrakis(4-bromophenyl)porphyrin as a ligand, and the coordinated central metal ion is a Cu, Co or Fe metal element.
[0011] Furthermore, the molar ratio of cuprous iodide or bis(triphenylphosphine)palladium dichloride in step 2) to the metal porphyrin compound in step 1) is 0.1-0.3:1; the reaction temperature in step 3) is 70-90° C., and the reaction time is 10-15 h.
[0012] Furthermore, the preparation method of the bismuth oxyhalide comprises the following steps: S1: dissolving potassium salt and bismuth nitrate in ethylene glycol organic solvent, wherein the potassium salt is potassium chloride, potassium bromide or potassium iodide; S2: The mixed solution obtained in step S1 is transferred to a reaction kettle, which is sealed and transferred to an oven for reaction at 140-180°C for 10-15h; S3: After the reaction is completed, the product is cooled to room temperature, centrifuged, washed with ethanol and distilled water for 1-3 times, and finally dried to obtain the bismuth halide.
[0013] Furthermore, in step S1, the molar ratio of the potassium salt to bismuth nitrate is 0.5-2:1, preferably 1:1, and the dispersed concentration of bismuth nitrate in the reaction solution of step S1 is 0.1-0.3 mmol / L.
[0014] The method for preparing a metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material comprises dispersing the bismuth oxyhalide and the metal porphyrin conjugated organic polymer in anhydrous ethanol at a mass ratio of 1:0.5-2, mixing and ultrasonically reacting for 1-3 hours to form a heterojunction, and after the reaction, centrifuging and drying the product to obtain the metal porphyrin-based conjugated organic polymer-bismuth oxyhalide composite material; the mass ratio of the bismuth oxyhalide and the metal porphyrin conjugated organic polymer is preferably 1:1.
[0015] The application of a metal porphyrin-based flexible conjugated organic polymer-halogen bismuth oxide composite material in a photocatalytic reduction of CO2 reaction, and the application method is: using the metal porphyrin-based flexible conjugated organic polymer-halogen bismuth oxide composite material as a photocatalyst, dispersing the photocatalyst in pure water at a concentration of 0.1-1g / L, transferring the mixed solution to a quartz reactor, using high-purity CO2 to evacuate the reactor and replace the gas to remove the air in the reaction system, and then introducing CO2 at a pressure of 20-200kPa into the reactor; after the system is balanced, using a 100-500W xenon lamp as a reaction light source for illumination, and maintaining the temperature of the reaction system at 2-10°C through a low-temperature constant temperature water bath system to carry out a photocatalytic CO2 reduction reaction.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1) The metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material prepared by the present invention includes the original flexible structure of the conjugated microporous polymer and the uniform distribution of metal ions, and further introduces bismuth oxyhalide to enrich more electrons, thereby having good light absorption performance and the performance of photocatalytic reduction of CO2 to produce high value-added products such as carbon monoxide and ethylene, and further improving the production of ethylene.
[0017] 2) The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth composite material prepared by the present invention not only has the advantages of high chemical stability, large specific surface area, good semiconductor performance, and simple synthesis process of conjugated microporous polymers, but also the porphyrin heterocycle can regulate its photophysical and chemical properties through central metal ion coordination and meso-position functional group modification, thereby optimizing the performance of the catalyst.
[0018] 3) Bismuth oxyhalides are enriched with more electrons, and bismuth oxyhalides and conjugated microporous polymers form an electronic tandem system. The rationally designed structure can regulate the distance between active sites, which helps to increase the yield of photocatalytic CO2 reduction to produce ethane, ethylene and other C2 compounds with higher added value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxycomposite material CMP-OPP(Cu):BiOCl=1:1 obtained in Example 1 and the Fourier transform infrared spectra of CMP-OPP(Cu) and BiOCl; Figure 2 The X-ray diffraction spectra of the metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material CMP-OPP(Cu):BiOCl=1:1 and BiOCl obtained in Example 1; Figure 3 The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxycomposite material CMP-OPP(Cu):BiOCl=1:1 obtained in Example 1 and the Eis electrochemical impedance spectroscopy diagram of CMP-OPP(Cu) and BiOCl; Figure 4 The metalloporphyrin-based flexible conjugated organic polymer-halogenated bismuth oxycomposite CMP-OPP(Cu):BiOCl=1:1 and IT transient photocurrent diagram of CMP-OPP(Cu) and BiOCl obtained in Example 1; Figure 5 The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxycomposite material CMP-OPP(Co):BiOCl=1:1 obtained in Example 2 and the Eis electrochemical impedance spectroscopy diagram of CMP-OPP(Co) and BiOCl; Figure 6 The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxide composite material CMP-OPP(Co):BiOCl=1:1 and IT transient photocurrent diagram of CMP-OPP(Co) and BiOCl obtained in Example 2; Figure 7 The Mott-Schottky curve of the metalloporphyrin-based flexible conjugated organic polymer-halogenated bismuth oxycomposite material CMP-OPP(Cu):BiOCl=1:1 obtained in 5) of Example 1; Figure 8 The photocatalytic experiment of the present invention was carried out according to the method of Example 3, and the catalytic carbon dioxide reduction performance results were obtained when the photocatalyst used was CMP-OPP (Cu): BiOCl = 1:1 in Example 1; Fig. 9 The photocatalytic experiment of the present invention was carried out according to the method of Example 3, and the catalytic carbon dioxide reduction performance results were obtained when the photocatalyst used was CMP-OPP(Co):BiOCl=1:1 of Example 2.
[0020] Fig.10 The photocatalytic experiment of the present invention was carried out according to the method of Example 3, and the catalytic carbon dioxide reduction performance results were obtained when the photocatalyst used was CMP-OPP(Fe):BiOCl=1:1 of Example 2.
[0021] Fig.11 The photocatalytic experiment was carried out according to the method of Example 3. The photocatalyst used was 8C-TBPP (Co) in Example 2: BiOCl = 1:1. The catalytic carbon dioxide reduction performance results were as follows: Fig.12 The photocatalytic experiment was carried out according to the method 1) of Example 3 of the present invention, and the photocatalysts used were CMP-OPP(Pt):BiOCl=1:1 and CMP-OPP(Mn):BiOCl=1:1 in the control test set in Example 3 to measure the catalytic carbon dioxide reduction performance results.
[0022] Fig.13 The photocatalytic experiment of the present invention was carried out according to the method 2) of Example 3, and the photocatalyst used was 4Br-PP(Cu):BiOCl=1:1 of Control Example 2 to catalyze the carbon dioxide reduction performance results.
[0023] Fig.14 This is a TEM image of bismuth oxychloride BiOCl prepared in step 2) of Example 1.
[0024] Fig.15 This is the HRTEM image of bismuth oxychloride BiOCl prepared in step 2) of Example 1. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0026] Example 1: Synthesis of a metalloporphyrin-based flexible conjugated organic polymer-halogenated bismuth oxyhalide composite material CMP-OPP (Cu): BiOCl = 1:1, comprising the following steps: 1) Add 5,10,15,20-tetrakis(4-bromophenyl)copperporphyrin (0.15 mmol) and 2,4,6-tris(2-propynyl-1-oxy)-1,3,5-triazine (0.2 mmol), catalyst bis(triphenylphosphine)palladium(II) chloride (0.022 mmol) and cuprous iodide (0.022 mmol), triethylamine (5 mL) and solvent tetrahydrofuran (5 mL) into a 25 mL three-necked flask. Under nitrogen atmosphere, heat the reaction solution to 85°C and stir continuously for 12 h. After the reaction is completed, cool to room temperature and collect the precipitate by filtration. Wash the precipitate with dichloromethane and methanol respectively until the filtrate is colorless, and then dry it in a vacuum oven at 80°C for 4 h to obtain the conjugated microporous polymer CMP-OPP (Cu); 2) Add bismuth nitrate pentahydrate (0.01mmol), potassium chloride (0.01mmol) and solvent ethylene glycol (68ml) into a 100ml tetrafluoroethylene reactor, seal the reactor and transfer it to an oven and heat it to 160℃ for 12h. After the reaction is completed, cool to room temperature, centrifuge the product, wash it three times with ethanol and distilled water, and then dry it in a vacuum oven at 50℃ for 6h to obtain bismuth oxychloride BiOCl.
[0027] The TEM and HRTEM images of the bismuth oxychloride BiOCl prepared in step 2 of Example 1 are shown in Fig.14 and Fig.15 ,from Figure 14-15 It can be seen that BiOCl is in the form of flakes, stacked layer by layer.
[0028] 3) Take 25 mg CMP-OPP (Cu) and 25 mg BiOCl in a beaker, disperse them in 30 ml anhydrous ethanol, place the beaker in an ultrasonic cleaner at 25°C for 2 hours, and wait for them to be fully dispersed. After the reaction is completed, centrifuge the product until the liquid is colorless, and then dry it in a vacuum at 60°C to obtain a metal porphyrin-based flexible conjugated organic polymer-halogen bismuth composite material CMP-OPP (Cu): BiOCl = 1:1.
[0029] 4) Preparation method of Eis and IT working electrodes: Preparation of S1 catalyst dispersion: 4 mg of catalyst powder was dispersed in 960 μL of anhydrous ethanol and 40 μL of Nafion binder, and the mixture was ultrasonically treated for 24 h to uniformly disperse the material to obtain a catalyst dispersion.
[0030] S2 Carbon cloth loading: 200 μL of the catalyst dispersion was added to the carbon cloth (0.5 cm × 2 cm) in 8 portions (25 μL × 8) to obtain about 0.8 mg cm -2 The catalyst loading is then placed in a vacuum oven and dried at 60°C before the electrochemical impedance spectroscopy test can begin.
[0031] S3 FTO glass loading: Take 200 μL of the catalyst dispersion and adhere it to the conductive surface of FTO glass (16.6×12.5 mm) in 8 times (25 μL×8), then put it into a vacuum oven and dry it at 60°C before starting the transient photocurrent test.
[0032] 5) Mott-Schottky test: S1: Using the metal porphyrin-based flexible conjugated organic polymer-halogen bismuth oxycomposite CMP-OPP(Cu):BiOCl=1:1 obtained in Example 1 as the sample to be tested, 4 mg of the sample to be tested is dispersed in a mixture of 400 µL ethanol and 600 µL water, and after ultrasonic dispersion, a conductive glass sheet is immersed in it, and after sufficient immersion, it is dried to obtain a conductive glass having the sample to be tested; S2: Three-electrode system test, the electrolyte is 0.1 mol / L Na2SO4 solution, the reference electrode is Ag / AgCl electrode, the counter electrode is platinum electrode, and the working electrode is conductive glass with the sample to be tested; S3: Test in a certain voltage range (-1 ~ 1 V vs Ag / AgCl), change the test frequency (1000, 1500 and 2000 Hz), and get the corresponding test curve. The test results at different frequencies are shown in Figure 7 .
[0033] Example 1: The Fourier transform infrared spectra of the metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth composite material CMP-OPP (Cu): BiOCl = 1:1, CMP-OPP (Cu), and BiOCl are as follows: Figure 1 As shown, by infrared analysis, the terminal alkyne CH peak in CMP-OPP(Cu):BiOCl=1:1 disappeared, the C-Br peak weakened, and the characteristic peaks of porphyrin and ligand appeared, proving that the material was successfully synthesized. The N-Cu peak proved that the porphyrin was successfully metallized, indicating that CMP-OPP(Cu) was successfully composited, and it contained Bi-Cl asymmetric stretching vibration peaks, indicating that BiOCl was successfully composited.
[0034] Example 1: Obtaining a metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxyhalide composite material CMP-OPP (Cu): BiOCl = 1:1, the XRD curve of BiOCl is as follows Figure 2 As shown in the figure, all the diffraction peaks of the composite material CMP-OPP(Cu):BiOCl=1:1 correspond to those of BiOCl. No characteristic peaks of other impurities or phases were detected, indicating that the BiOCl composite in the preparation of CMP-OPP(Cu):BiOCl=1:1 was successfully prepared.
[0035] The metal porphyrin-based flexible conjugated organic polymer-halogenated bismuth oxyhalide composite material CMP-OPP(Cu):BiOCl=1:1, CMP-OPP(Cu), and BiOCl were used as catalysts in Example 1, and a carbon cloth electrode was prepared according to the S2 method in step 4) of Example 1. The prepared carbon cloth electrode was used to perform an Eis electrochemical impedance test. The Eis electrochemical impedance results of the CMP-OPP(Cu):BiOCl=1:1, CMP-OPP(Cu), and BiOCl catalysts were shown in FIG. Figure 3 As shown, it can be seen that the arc radius of the polymer CMP-OPP(Cu):BiOCl=1:1 is smaller than that of CMP-OPP(Cu) and BiOCl. In the Nyquist plot, the arc radius is positively correlated with the charge impedance of the corresponding material. It can be seen that the polymer has a smaller interface charge transfer impedance, which is beneficial to the interface charge transfer process in the photocatalytic process, thereby improving the photocatalytic performance.
[0036] Example 1: A metal porphyrin-based flexible conjugated organic polymer-halogen bismuth oxide composite material CMP-OPP (Cu): BiOCl = 1:1 and CMP-OPP (Cu) and BiOCl were used as catalysts, respectively. A FTO glass electrode was prepared according to the S3 method of step 4) of Example 1. The prepared FTO glass electrode was used to perform a transient photocurrent test. The results are as follows: Figure 4 As shown, it can be seen that the photocurrent response of the polymer CMP-OPP(Cu):BiOCl=1:1 is significantly stronger than that of CMP-OPP(Cu) and BiOCl, indicating that these composite samples have excellent photocurrent response and good photoresponse stability. It also shows that they are more conducive to the generation and migration of photoinduced charges in the photocatalytic process, thereby improving the reaction efficiency of CO2 reduction.
[0037] Example 1 Obtaining a Metalloporphyrin-Based Flexible Conjugated Organic Polymer-Bismuth Oxyhalide Composite Material The Mott-Schottky curve of CMP-OPP(Cu):BiOCl=1:1 is shown in Figure 7 As shown, the ordinate of the curve is the inverse of the square of the capacitance. The semiconductor characteristics can be judged by the curve. The positive slope of the straight line part of the curve indicates that the material is an n-type semiconductor.
[0038] Example 2: Synthesis of metal porphyrin-based flexible conjugated organic polymer-halogen bismuth composite materials CMP-OPP(Co):BiOCl=1:1 and CMP-OPP(Fe):BiOCl=1:1. The synthesis steps are repeated in Example 1, with the only difference being that "in step 1), 5,10,15,20-tetrakis(4-bromophenyl)copperporphyrin is replaced with an equal molar amount of 5,10,15,20-tetrakis(4-bromophenyl)cobaltporphyrin or 5,10,15,20-tetrakis(4-bromophenyl)ironporphyrin", and the other conditions remain unchanged. The intermediate products metal porphyrin-based conjugated organic polymers CMP-OPP(Co) and CMP-OPP(Fe) are prepared respectively, as well as the metal porphyrin-based conjugated organic polymer-halogen bismuth composite materials CMP-OPP(Co):BiOCl=1:1 and CMP-OPP(Fe):BiOCl=1:1 are finally prepared.
[0039] The synthesis steps of the metal porphyrin-based flexible conjugated organic polymer-halogen bismuth composite material 8C-TBPP (Co): BiOCl = 1: 1 are repeated in Example 1, except that "in step 1), 5, 10, 15, 20-tetrakis (4-bromophenyl) copper porphyrin is replaced by an equal molar amount of 5, 10, 15, 20-tetrakis (4-bromophenyl) cobalt porphyrin, and 2,4,6-tris (2-propyne-1-oxy) -1,3,5-triazine is replaced by an equal molar amount of 1,8-octanediol", and the other conditions remain unchanged to prepare the intermediate product metal porphyrin-based conjugated organic polymer 8C-TBPP (Co), and finally the metal porphyrin-based conjugated organic polymer-halogen bismuth composite material 8C-TBPP (Co): BiOCl = 1: 1 is prepared.
[0040] Example 2 A flexible metal porphyrin conjugated organic polymer-halogen bismuth oxide composite material CMP-OPP (Co): BiOCl = 1:1 and CMP-OPP (Co) and BiOCl were used as catalysts, respectively. A carbon cloth electrode was prepared according to the S2 method of step 4) of Example 1. The prepared carbon cloth electrode was used to perform an Eis electrochemical impedance test. The Eis electrochemical impedance test results are as follows: Figure 5 As shown, it can be seen that the arc radius of the polymer CMP-OPP(Co):BiOCl=1:1 is smaller than that of CMP-OPP(Co) and BiOCl. It can be seen that the polymer has a smaller interfacial charge transfer impedance, which is beneficial to the interfacial charge transfer process in the photocatalytic process, thereby improving the photocatalytic performance.
[0041] Example 2: A metal porphyrin-based flexible conjugated organic polymer-halogen bismuth oxide composite material CMP-OPP (Co): BiOCl = 1:1 was obtained, and CMP-OPP (Co) and BiOCl were used as catalysts, respectively. A FTO glass electrode was prepared according to the S3 method of step 4) of Example 1. The prepared FTO glass electrode was used to perform a transient photocurrent test. The transient photocurrent test comparison results are shown in FIG. Figure 6 As shown, it can be seen that the photocurrent response of the polymer is significantly stronger than that of CMP-OPP(Co) and BiOCl, indicating that these composite samples have excellent photocurrent response and good photoresponse stability. It also shows that they are more conducive to the generation and migration of photoinduced charges in the photocatalytic process and improve the reaction efficiency of CO2 reduction.
[0042] Example 3: 30 mg of photocatalyst and 50 mL of pure water were added to a quartz reactor, and the materials were evenly dispersed by ultrasound, and then the reactor was connected to the photocatalytic test system. The magnetic stirrer at the bottom of the reactor was turned on, and the reactor was vacuumed and replaced with gas three times using high-purity CO2 to remove the air in the reaction system, and CO2 was introduced again to keep the CO2 pressure in the reaction system at about 80 kPa. After the system was balanced, a 300 W xenon lamp was used as the reaction light source, and the temperature of the reaction system was maintained at 5°C by a low-temperature constant temperature water bath system. The gas chromatograph automatically took samples for analysis every 30 min or 1 h, and calculated the yield of each main component in the product of photocatalytic reduction of CO2 at different reaction times. The unit of yield was the micromolar content of each component obtained per gram of catalyst.
[0043] According to the above catalytic experiment process, when the photocatalysts are respectively CMP-OPP(Cu):BiOCl=1:1 and CMP-OPP(Cu) in Example 1, the relationship between the yield of the photocatalytic reduction product and time is shown in FIG. Figure 8 ; When the photocatalysts are respectively CMP-OPP(Co):BiOCl=1:1 and CMP-OPP(Co) of Example 2, the relationship between the yield of the photocatalytic reduction product and the time is shown Fig. 9 ; When the photocatalysts are respectively CMP-OPP(Fe):BiOCl=1:1 and CMP-OPP(Fe) of Example 2, the relationship between the yield of the photocatalytic reduction product and time is shown Fig.10 , Figure 8-Figure 10 The relationship between the production of photocatalytic reduction products CO and C2H4 and time was recorded.
[0044] pass Figure 8 , Fig. 9 and Fig.10It can be seen that the metal porphyrin-based conjugated organic polymer-halogen bismuth composite material prepared by the method of Examples 1 and 2 is beneficial to increase the yield of C2 compounds with higher added value such as ethylene in the product when applied to the photocatalytic CO2 reduction reaction. Secondly, the type of metal will affect the photocatalytic CO2 yield, and different metals have different effects. It can be seen that the photocatalytic activity is better when the central metal of the photocatalyst is Co or Cu.
[0045] According to the above catalytic experimental process, when the photocatalysts are 8C-TBPP(Co):BiOCl=1:1 and 8C-TBPP(Co) in Example 2, the yields of the photocatalytic reduction products CO and C2H4 change with time respectively. Fig.11 .contrast Fig.11 and Fig. 9 It can be seen from the experimental results that the preparation conditions of the metal porphyrin-based conjugated organic polymer of the photocatalyst have a great influence on the photocatalytic CO2 yield. When 2,4,6-tris(2-propynyl-1-oxy)-1,3,5-triazine is used to prepare the metal porphyrin-based conjugated organic polymer, the photocatalytic activity is better improved.
[0046] Control Example 1: Synthesis of metal porphyrin-based flexible conjugated organic polymer-halogen bismuth composite materials CMP-OPP(Pt):BiOCl=1:1 and CMP-OPP(Mn):BiOCl=1:1. The synthesis steps were repeated in Example 1, with the only difference being that "in step 1), 5,10,15,20-tetrakis(4-bromophenyl)copperporphyrin was replaced with an equal molar amount of 5,10,15,20-tetrakis(4-bromophenyl)platinumporphyrin or 5,10,15,20-tetrakis(4-bromophenyl)manganeseporphyrin", and the other conditions remained unchanged. Finally, metal porphyrin-based conjugated organic polymer-halogen bismuth composite materials CMP-OPP(Pt):BiOCl=1:1 and CMP-OPP(Mn):BiOCl=1:1 were obtained, respectively.
[0047] According to the catalytic experiment process of Example 3, when the photocatalysts are respectively CMP-OPP (Pt): BiOCl = 1:1 and CMP-OPP (Mn): BiOCl = 1:1 of Control Example 1, the relationship between the yield of the photocatalytic reduction product and time is summarized as follows: Fig.12 middle.
[0048] Comparative Example 2: Metalloporphyrin-bismuth oxyhalide composite material 4Br-PP(Cu):BiOCl=1:1, the synthesis steps of which are to take 25 mg of 5,10,15,20-tetrakis(4-bromophenyl)copperporphyrin and 25 mg of BiOCl in a beaker, disperse them in 30 ml of anhydrous ethanol, place the beaker in an ultrasonic cleaner at 25°C for 2 hours, and after the dispersion is fully uniform, after the reaction is completed, centrifuge the product until the liquid is colorless, and then vacuum dry it at 60°C to obtain the metalloporphyrin-bismuth oxyhalide composite material 4Br-PP(Cu):BiOCl=1:1.
[0049] According to the catalytic experiment process of Example 3, when the photocatalyst is 4Br-PP(Cu):BiOCl=1:1 of Control Example 2, the relationship between the yield of the photocatalytic reduction product and time is summarized as follows: Fig.13 middle.
[0050] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A metalloporphyrin-based flexible conjugated organic polymer-halogenated bismuth oxide composite material, characterized in that The composite material is a heterojunction structure formed by bismuth oxyhalide and a metal porphyrin-based conjugated organic polymer. The metal porphyrin-based conjugated organic polymer is formed by coupling reaction between an aromatic halogen atom in a metal porphyrin compound and an alkynyl group of a triazine derivative with an alkynyl group, or is a conjugated microporous polymer formed by coupling reaction between an aromatic halogen atom in a metal porphyrin compound and a hydroxyl group of 1,8-octanediol. The central metal ion in the metal porphyrin compound is a Cu, Co or Fe metal element. The bismuth oxyhalide is a crystalline layered structure formed by alternating stacking of bismuth oxygen layers and halogen layers, and the layers are connected by van der Waals forces, wherein X represents a Cl, Br or I halogen element.
2. A metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 1, characterized in that The preparation method of the metal porphyrin conjugated organic polymer comprises the following steps: Step 1: dissolving a metal porphyrin compound and a triazine derivative with an alkynyl group or 1,8-octanediol in an organic solvent containing triethylamine; Step 2: adding catalysts cuprous iodide and bis(triphenylphosphine)palladium dichloride; Step 3: Heat the oil bath to 60-120°C under nitrogen atmosphere and continue stirring to react for 6-24 hours; Step 4: After the reaction in step 3 is completed, the metalloporphyrin conjugated organic polymer is obtained by filtering, washing and drying.
3. A metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 2, characterized in that In step 1, the molar ratio of the metal porphyrin compound to the triazine derivative with an alkynyl group or 1,8-octanediol is 1.1-1.5:1, the volume ratio of the triethylamine to the organic solvent is 0.5-2:1, and the dispersed concentration of the metal porphyrin compound in the reaction solution of step 1 is 0.002-0.02 mol / L.
4. A metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 2, characterized in that The metal porphyrin compound uses 5,10,15,20-tetrakis(4-bromophenyl)porphyrin as a ligand, and its coordinated central metal ion is a Cu, Co or Fe metal element; the triazine derivative with an alkynyl group is 2,4,6-tris(2-propynyl-1-oxy)-1,3,5-triazine; the molar ratio of cuprous iodide or bis(triphenylphosphine)palladium dichloride in step 2 to the metal porphyrin compound in step 1 is 0.1-0.3:1; the reaction temperature in step 3 is 70-90°C, and the reaction time is 10-15h.
5. A metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 1, characterized in that The preparation method of the bismuth oxyhalide comprises the following steps: S1: dissolving potassium salt and bismuth nitrate in ethylene glycol organic solvent, wherein the potassium salt is potassium chloride, potassium bromide or potassium iodide; S2: The mixed solution obtained in step S1 is transferred to a reaction kettle, which is sealed and transferred to an oven for reaction at 140-180°C for 10-15h; S3: After the reaction is completed, the product is cooled to room temperature, centrifuged, washed with ethanol and distilled water for 1-3 times, and finally dried to obtain the bismuth halide.
6. A metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 5, characterized in that In step S1, the molar ratio of the potassium salt to bismuth nitrate is 0.5-2:1, and the dispersed concentration of bismuth nitrate in the reaction solution of step S1 is 0.1-0.3 mmol / L.
7. The method for preparing a metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material according to claim 1, characterized in that The bismuth oxyhalide and the metal porphyrin conjugated organic polymer are dispersed in anhydrous ethanol at a mass ratio of 1:0.5-2, mixed and ultrasonically reacted for 1-3 hours to form a heterojunction. After the reaction, the product is centrifuged and dried to obtain a metal porphyrin-based conjugated organic polymer-bismuth oxyhalide composite material.
8. The method for preparing a metal porphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material according to claim 7, characterized in that The mass ratio of the bismuth oxyhalide to the metal porphyrin conjugated organic polymer is 1:
1.
9. Use of a metalloporphyrin-based flexible conjugated organic polymer-bismuth oxyhalide composite material as claimed in claim 1 in a photocatalytic reduction of CO2 reaction.
10. The use according to claim 9, characterized in that The metal porphyrin-based flexible conjugated organic polymer-halogen bismuth composite material is used as a photocatalyst, the photocatalyst is dispersed in pure water at a concentration of 0.1-1g / L, the mixed solution is transferred to a quartz reactor, the reactor is evacuated and gas is replaced using high-purity CO2 to remove the air in the reaction system, and then CO2 at a pressure of 20-200kpa is introduced into the reactor; after the system is balanced, a 100-500W xenon lamp is used as a reaction light source for illumination, and the temperature of the reaction system is maintained at 2-10°C through a low-temperature constant temperature water bath system to carry out a photocatalytic CO2 reduction reaction.
Citation Information
Patent Citations
Metalloporphyrin functional poly 4-vinylpyridine-styrene composite crosslinked microsphere catalyst and preparation method thereof
CN101632942A
Preparation method and application of BiOBr / COF composite photocatalyst
CN111822055A
Porphyrin-based flexible conjugated microporous polymer as well as preparation method and application thereof
CN117089050A
Antitumor agents and process for producing the same
US20040234495A1